Pregnancy-associated plasma protein-A truncation limits in antenatal screening for trisomy 18. (March 2018) - Bestwick, JP; Huttly, WJ; Wald, NJ
Upper and lower truncation limits are commonly applied to quantitative markers used in medical screening tests. We here examine data on 375 trisomy 18 and 522, 081 unaffected singleton pregnancies, to determine if the lower truncation limit should be set below the previously specified 0.2 multiples of the median. A lower truncation limit of 0.15 would reduce the underestimation of the risk of having a trisomy 18 pregnancy in about 50% of affected pregnancies and would lead to an estimated 10 percentage point increase in the detection rate, with only a very small increase in the false-positive rate.